Ventricular Arrhythmias Underlie Sudden Death in Rats With Heart Failure and Preserved Ejection Fraction. (August 2018) - Cho, Jae Hyung; Zhang, Rui; Aynaszyan, Stephan; Holm, Kevin; Goldhaber, Joshua I.; Marbán, Eduardo; Cingolani, Eugenio
Abstract : Background: Heart failure (HF) with preserved ejection fraction (HFpEF) is increasingly common clinically, now rivaling or exceeding HF with reduced ejection fraction. Sudden death is the leading mode of exodus in patients with HFpEF, but the underlying causes are largely unknown. Using ambulatory recordings in a rat model, we test the hypothesis that ventricular arrhythmias (VA) underlie sudden death in HFpEF. Methods: Dahl salt-sensitive rats (7 weeks of age) were fed a high-salt diet to induce HFpEF (n=13) or a normal-salt diet (controls, n=9). Transthoracic echocardiography was performed to check systolic and diastolic function at 14 to 18 weeks of age. Telemetric electrocardiographic recordings were analyzed for QT interval duration, burden of premature ventricular contractions, spontaneous VA, and heart rate variability. Survival was monitored twice daily. Results: High-salt–fed rats with clear diastolic dysfunction, preserved ejection fraction, and HF signs were diagnosed with HFpEF at 14 to 15 weeks of age. QT and QTc intervals were prolonged in HFpEF rats compared with controls. Heart rate variability was reduced in HFpEF rats compared with controls. Spontaneous VA were more prevalent in HFpEF rats (6/13=46.1% versus 0/9=0% in controls; P <0.05), and sudden death was observed in 4 of 13 HFpEF rats. Three of the 4 sudden deaths were associated with VA as the terminal rhythm. Conclusions: In this rat model with phenotypically verified HFpEF, sudden death was common and generally associated with VA. Further clinical studies are warranted to determine whether these insights translate to sudden death in HFpEF patients. Abstract : Supplemental Digital Content is available in the text.